Modern Social Behaviors in Fiction of Dr. Izharullah Izhar - Dr. Subhanullah; Dr. Yasmeen Sultan (Zaban-o-Adab, 2022)
Since the inception of the twentieth century to the second decade of the present century, the genre of fiction in Urdu literature has successfully evolved through new experiments and variations in terms of subject, material, art and technique. New dimensions have emerged. Dr. Izharullah Izhar's legendary collection "Aakhri afsana" is an important addition to the mythical literature of the twenty first century. Due to the problems, created by the revolution and the modern questions related to philosophy and religion, he is suffering from skepticism, uncertainty and severe mental and emotional turmoil. The fiction writer not only describes these modern problems and complexities in "Aakhri afsana" but also tries to find answers to some extent. The article under review examines the extent to which fiction writer have been successful in their endeavors in terms of art and thought.